A Novel Long-Term Graves' Disease Animal Model Confirmed by Functional Thyrotropin Receptor Antibodies. Issue 1 (23rd December 2020) - Diana, Tanja; Holthoff, Hans-Peter; Fassbender, Julia; Wüster, Christian; Kanitz, Michael; Kahaly, George J.; Ungerer, Martin
Abstract : Introduction: A novel long-term murine model for Graves' disease (GD) using repeated, long-term immunizations with recombinant adenovirus expressing the extracellular A-subunit of the human thyrotropin receptor (Ad-TSHR) was applied to evaluate the functional anti-TSHR-antibody (TSHR-Ab) profile. Methods: BALB/c mice received 7 immunizations with either 10 10 plaque-forming units of Ad-TSHR or control Ad-GFP. Naïve (nonimmuized native) mice were also studied. Three 3-weekly immunizations were followed by 4-weekly boosts until the 7th immunization. Blocking (TBAb) and stimulating (TSAb) TSHR-Ab were measured with bioassays. Assay cut-offs for TBAb/TSAb were at 34% inhibition and a specimen-to-reference ratio (SRR) of 140%. Results: Nineteen (8 Ad-TSHR-, 4 Ad-GFP-immunized, and 7 native) mice were investigated. All native mice were negative for TSHR-binding inhibitory immunoglobulins (TBII) prior to immunization. Native and Ad-GFP mice were negative in weeks 17 and 27 for TBII and TBAb/TSAb. In native mice, the free thyroxine (fT4) levels (median [25th percentile; 75th percentile]) were in the upper normal range (1.2 ng/mL [1.1; 1.6]) prior to immunization, at weeks 17 (2.2 ng/mL [2.1; 2.4]) and 27 (1.4 ng/mL [1.1; 1.7]), respectively. In contrast, in Ad-TSHR-immunized mice, fT4 values were markedly increased at weeks 17 (4.4 ng/mL [3.9; 6]) and 27 (4.5 ng/mL [4.2; 6]) compared to those in Ad-GFP mice (2 ng/mL [1.8; 2.1] and 1.4 ng/mL [1.1; 1.6]), respectively ( p = 0.0008, p = 0.001). In contrast, at week 17, in Ad-TSHR mice, the mean TBII, TBAb, and TSAb levels were 40 IU/L (40; 40); 62% inhibition (38; 69), and 116% SRR (97; 185), respectively; at week 27, they were 40 IU/L (39; 40); 65% inhibition (34; 80) and 95% SRR (63; 187), respectively. Three serum samples from Ad-TSHR mice (38%) demonstrated dual TBAb/TSAb positivity. Conclusions: TBAb/TSAb were highly prevalent in Ad-TSHR-immunized mice, thus confirming the successful establishment of a novel, long-term murine model for GD. All TBAb- and TSAb-positive Ad-TSHR-immunized mice were TBII-positive. Thus, the binding immunoassay did not differentiate between TSHR-Ab functionality.